Nutrient Film Hydroponic System Techniques for Pid-Based Strawberry Growth - Muhammad Afif Abdullah; Harianto; Musayyana; Pauladie Susanto (JEECS (Journal of Electrical Engineering and Computer Sciences), 2022)
Surabaya is an urban area with limited land for farming, because there are many buildings. Farming requires a largearea and fertile soil. With the development of agricultural technology today, there is a new method of planting calledHydroponics. There are several types of hydroponic systems, namely Aeroponics (fog system) and Nutrient FilmTechnique (NFT). In this article, the writer uses NFT technique. NFT is a system that has a farming concept bychanneling nutrients to plant roots in a film or thin so that plants get food nutrients, namely water and oxygen. Theadvantage of using this NFT system is that it makes it easier to control plant nutrients and plant growth is fasterbecause plant roots are free to absorb nutrients to the maximum. From the results of the research conducted, the pHsetpoint value was 6.0. From the results of the research conducted, set point pH values of 6.4 and 5.8. From the testresults, the Ziegler Nichols method of type 1 for a setpoint of 6.4 gets a value of L=3 and T=22.44 and a setpoint valueof 5.8 gets a value of L = 3 and T = 23.76. After that, the setpoint 6.4 got the value of Kp = 8.976 Ki = 1.496 Kd =13,464 and the setpoint of 5.8 got the value of Kp = 9.504 Ki = 1.584 Kd = 14,256. 1. The setpoint value of 6.4overshoot is 8.37% rise time 20 s, and settling time is 45 s. The setpoint value of 5.8 overshoot is 6.89% rise time 25s, and settling time is 55 s.